Avaliação da potencialidade de rochas xistosas para aplicações como rochas ornamentais e de revestimento - Marcela Mourao Moura (2012)
The present study established the potential of applying a set of foliated rocks as building stones, based on description of their petrographic characteristics and geomechanical properties. The evaluated rocks consist of shale and peraluminous schists, ultramafic schist and greenschist, generated under different conditions of metamorphism, in the state of Minas Gerais. These lithotypes have a strong planar anisotropy and are composed primarily of submillimeter crystals. The automatic measurement of geometrical parameters of the grains, based on digital image processing, was a reliable basis for the evaluation of textural parameters and interpretation of its influence on the geomechanical behavior of foliated rocks. The present study investigated the relationship between the metamorphic grades, reflected in the intrinsic properties of these rocks - mineralogical composition and texture, and its resistance when subjected to mechanical stress. The values and relationships between the geomechanical parameters obtained in this study confirm the importance and contribution of this work to the knowledge of building stones. Evaluations of foliated rocks in historic buildings associated with petrographic and geomechanical parameters obtained in this study contain the information necessary to indicate the most appropriate forms of use of foliated rocks and prove its viability as building stone.